Molecular Mechanics Study of the Cyclic and Unsymmetric Diborane(4) Compounds - N. Rendtorff; E. A. Castro (The Scientific World Journal)
The results of a theoretical study on the structure of some diborane(4) compounds are presented in order to analyze the issue related to the relative stabilities of the 1,1- vs. 1,2-isomers. Through the employment of the molecular mechanics method, characteristic distances and angles are given and they are compared with available experimental data. In order to rationalize the results, the different energy components are discussed in a comparative fashion. We find a rather satisfactory agreement between theoretical and experimental data. Some possible future extensions are pointed out to complement this sort of analysis.